2000
DOI: 10.1128/aac.44.4.1102-1107.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Sitafloxacin (DU-6859a) and Six Other Fluoroquinolones against 8,796 Clinical Bacterial Isolates

Abstract: The in vitro activities of sitafloxacin, ciprofloxacin, trovafloxacin, levofloxacin, clinafloxacin, gatifloxacin, and moxifloxacin against 5,046 gram-negative bacteria, 3,344 gram-positive cocci, and 406 anaerobes were determined. Sitafloxacin was the most active agent against gram-positive cocci and anaerobes. Against Enterobacteriaceae and nonfermenters, its activity was either equivalent to or better than that of clinafloxacin.Sitafloxacin (DU-6859a) is a new fluoroquinolone active against gram-positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
70
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 19 publications
6
70
1
5
Order By: Relevance
“…Many new fluoroquinolones have been tested for in vitro activities against gram-positive, gram-negative, and anaerobic bacteria previously (4,9). Similarly, other studies have demonstrated the good activity of new fluoroquinolones against various anaerobic species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many new fluoroquinolones have been tested for in vitro activities against gram-positive, gram-negative, and anaerobic bacteria previously (4,9). Similarly, other studies have demonstrated the good activity of new fluoroquinolones against various anaerobic species.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance is becoming less predictable and may fluctuate from one medical center to another, as well as from one geographic region to another (1)(2)(3)(4)(7)(8)(9). The increasing resistance among several species emphasizes the need to survey the susceptibility patterns of these organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the mutant selection window (MSW) is an antimicrobial concentration range extending from the minimal concentration required to block the growth of wild-type bacteria up to that required to inhibit the growth of the single-step mutant, and the upper boundary is also called the MPC 1,4 . Sitafloxacin is a new fluoroquinolone that has been reported to have a broader spectrum, and the greater activity against quinolone-resistant strains than that of other quinolones 5 . The purpose of this study was to evaluate the in vitro activity of sitafloxacin and compare its MPC and MSW to those of levofloxacin, moxifloxacin, garenoxacin, and ciprofloxacin.…”
mentioning
confidence: 99%
“…NC_000907), which was used as the wild-type standard strain in this study. The MPC is defined as the fluoroquinolone concentration at which no colony was recovered when more 4 than 10 10 cells were applied to agar plates, and generally, it is also defined the lower limit of the MSW equal to the MIC 5 . The MPC methodology was adapted from the method outlined by Blondeau et al 1 .…”
mentioning
confidence: 99%